Anomalous anisotropy of re-entrant Ni77Mn23 film - (:unkn) unknown (IOP PUBLISHING LTD, 1997)
Re-entrant polycrystalline Ni77Mn23 films, 600 Angstrom thick, grown on a quartz substrate by using an electron beam evaporation technique, have been investigated. A spin-wave resonance (SWR) technique has been used to study the magnetic properties of the films. The SWR spectra exhibit highly anisotropic behaviour with respect to the film normal. When the sample is rotated around the film normal in a fixed applied field, both the resonance fields and the line-shapes are changed. This unexpected behaviour - for a polycrystalline film - has been attributed to a growth-induced geometric (oblique) anisotropy. The SWR spectra have been successfully analysed by using this oblique anisotropy term in addition to usual magnetocrystalline effective bulk, surface, and unidirectional anisotropy terms in the magnetic free energy. A substantial and temperature-dependent growth-induced geometric anisotropy has been obtained, beside the usual bulk and surface anisotropies. A strong correlation between the surface and oblique anisotropy has been found. This correlation has been attributed to a manifestation of the influence of easy-plane surface anisotropy along the fibre axes of individual grains on the effective magnetic anisotropy energy.
Keywords: SPIN-WAVE RESONANCE; NI-MN ALLOYS; SURFACE ANISOTROPY; THIN-FILMS; REENTRANT